Pengaruh Pemberian Jus Buah Naga terhadap Perubahan Kadar Hemoglobin Ibu Hamil di Wilayah Kerja Puskesmas Kota Baru Kabupaten Indragiri Hilir - Herlina, Herlina; Haiyanti, Reni; Lestari, Siti (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The prevalence of iron deficiency anemia in pregnancy is around 95% due to iron deficiency (iron deficiency anemia). Anemia is the second main cause of maternal death, accounting for around 12.8% of maternal deaths due to postpartum hemorrhage. One way to overcome anemia in pregnancy is to consume dragon fruit regularly, in addition to consuming Fe tablets that have been given by midwives or health workers. Giving dragon fruit juice is effective in increasing Hb levels in pregnant women. The research design used in this study was a pre-test and post-test with control group design in the Kota Baru Health Center Working Area, Indragiri Hilir Regency. A population of 230 pregnant women with a sampling technique using simple random sampling obtained 32 respondents (16 intervention groups and 16 control groups). Data analysis used the independent t-test. The results of this study indicate that there is an effect of giving dragon fruit juice on changes in hemoglobin levels of pregnant women in the Kota Baru Health Center Working Area, Indragiri Hilir Regency. Dragon fruit can be used as a supplement to increase hemoglobin levels in pregnant women to treat anemia.